Muscle involvement in systemic lupus erythematosus: multimodal ultrasound assessment and relationship with physical performance. (25th March 2022) - Di Matteo, Andrea; Smerilli, Gianluca; Cipolletta, Edoardo; Wakefield, Richard J; De Angelis, Rossella; Risa, Anna Maria; Salaffi, Fausto; Farah, Sonia; Villota-Eraso, Catalina; Maccarrone, Vincenzo; Filippucci, Emilio; Grassi, Walter
Abstract: Objectives: The objectives of this study were (1) to explore US findings for muscle mass, muscle quality and muscle stiffness in SLE patients and healthy subjects; (2) to investigate the relationship between the US muscle findings and physical performance in SLE patients and healthy subjects. Methods: Quadriceps muscle thickness was used for assessment of muscle mass, muscle echogenicity (using a visual semi-quantitative scale and grayscale analysis with histograms) for assessment of muscle quality, and point shear-wave elastography (SWE) for assessment of muscle stiffness in 30 SLE patients (without previous/current myositis or neuromuscular disorders) and 15 age-, sex- and BMI-matched healthy subjects. Hand grip strength tests and short physical performance battery (SPPB) tests were carried out in the same populations. Results: No difference was observed between SLE patients and healthy subjects for quadriceps muscle thickness (35.2 mm ±s.d. 6.8 vs 34.8 mm ± s.d. 6.0, respectively, P  = 0.79). Conversely, muscle echogenicity was significantly increased in SLE patients (visual semi-quantitative scale: 1.7 ± s.d. 1.0 vs 0.3 ± s.d. 0.5, respectively, P  < 0.01; grayscale analysis with histograms: 87.4 mean pixels ± s.d. 18.8 vs 70.1 mean pixels ± s.d. 14.0, respectively, P  < 0.01). Similarly, SWE was significantly lower in SLE patients compared with healthy subjects {1.5 m/s [interquartile range (IQR) 0.3] vs 1.6 m/s (IQR 0.2), respectively, P  = 0.01}. Muscle echogenicity was inversely correlated with grip strength (visual semi-quantitative scale, Rho : –0.47, P  = 0.01; grayscale analysis with histograms, Rho : –0.41, p  < 0.01) and SPPB (visual semi-quantitative scale, Rho : –0.50, P  < 0.01; grayscale analysis with histograms Rho : –0, 46, P  < 0.01). Conclusions: US assessment of muscle echogenicity and stiffness is useful for the early detection of muscle involvement in SLE patients.